Survey on the deployment and design for regular topology structures in wireless sensor networks - Wen-xiang LI; Ya-jie MA; Jun XU; Jian-feng YANG (Tongxin xuebao)
In wireless sensor networks,such regular topology structures as Square,Hexagon and Triangle could fully cover the area to be monitored,provide accurate positioning for special events,and achieve better network performance.In order to provide valuable guidelines for WSN design and optimization,related works on regular topology structures was surveyed.By the analysis on the index of Area per Node,the deployment method and efficiency of regular topology structures under such cases as full coverage,k-coverage and l-connectivity was explored.the performance,variation and application scenarios in such aspects as network connectivity,energy consumption,transmission performance,routing scheme and MAC protocol was summarized.The optimal application conditions for each structure together with several directions for further research were proposed.